Fatty Acid Composition of Rickettsiae - Tzianabos, Theodore (1981)
The fatty acid compositions of selected strains of rickettsiae were studied by gas-liquid chromatography. The profiles of all the rickettsiae except Coxiella burnetii were qualitatively similar. The fatty acid composition of C. burnetii was similar to that of certain Legionella species.